A SOCIOLOGIST IN INTERDISCIPLINARY RESEARCH - Oleg Ivanovich (Дискурс)
Situation with a role of sociologists in interdisciplinary researches is characterized in the article. The author offers a system of basic principles of methodological organization of interdisciplinary researches, considers possible roles of a sociologist in collective interdisciplinary scientific search and the main forms of realization of interdisciplinary researches. The author suggests to distinguish the potential of interdisciplinary object study and really achieved level of interdisciplinarity of research.